FRI0128 Efficacy and Safety of 23-Valent Pneumococcal Vaccine in SLE Patients (Preliminary Results). (15th July 2016) - Tarasova, G.M.; Belov, B.S.; Naumtseva, M.S.; Soloviev, S.K.; Aseeva, E.A.; Klyukvina, N.G.; Popkova, T.V.; Alexandrova, E.N.; Novikov, A.A.
Abstract : Background: Comorbid infections (CI) appear to have detrimental effect on the course and the prognosis of systemic lupus erythematosus (SLE) as current rheumatology practice indicates. These CIs become not only the predictors of lethal outcome, but also number two among known causes of death after the activity of the disease as the cause number one. Pneumonia remains the leading clinical entity among infectious diseases in SLE pts, thus immunization of SLE pts with pneumococcal vaccine is an essential issue in clinical practice. Objectives: To study the relevance of 23-valent pneumococcal vaccine for immunization of SLE pts, receiving immunosuppressive therapy. Methods: The study included 24 SLE patients, 22 females, 2 males aged 19 - 62 years. Low disease activity was documented in 18 patients, moderate – in 3 patients, and drug-induced remission – in 3. 23 patients were getting glucocorticoids (GCs) (4 pts - metipred - 24 mg/day.), 19 pts – plaquenil 200–400 mg/day, 13 pts – cytostatic (CS) drugs, including 8 – mycophenolate mofetil 1–2 g/day, 3 – methotrexate 10–15 mg/week, 1- mycophenolic acid 1080 mg/day, 1-azathioprine 50 mg. Eight patients were on biologic diseases modifying anti rheumatic drugs (bDMARDs), including 5 – on rituximab at 500–1000 mg per course of treatment, 3 – on belimumab at doses of 720, 480 and 400 mg per infusion. One or two episodes of lower respiratory tract infections occurred in 4 pts during the year prior to vaccination. One dose (0, 5 ml) of 23-valent polysaccharide pneumococcal vaccine was administered subcutaneously without discontinuation of GCs and CSs, or 1 months before initiation of bDMARDs /6 mo after the last injection of bDMARDs. The duration of FUP was 1–10 months. Results: Vaccine tolerability was good in 10 (41, 7%) patients, local injection site reactions of varying intensity without accompanying fever were registered in 13 (54, 2%) patients, lasting 2 to 7 days; they completely resolved spontaneously without additional treatment. One patient (4, 2%) developed hyperergic reaction in the form of Arthus phenomenon (hyperemia, induration and swelling of the injection site up to 10 cm in diameter, pain and subfebrile fever). These symptoms subsided within 7 days with 3 days intake of antihistaminic drug and local use of GCs. These reactions were typical and assessed as having casual relationship with vaccination. In one patient with SLE and interstitial lung disease, manifesting as recurrent bronchitis and pneumonia, non-severe bilateral bronchopneumonia was documented 9 months post-vaccination, which resolved after 7 days of antibiotic therapy in the out-patient setting. One patient developed post- stress non-severe SLE exacerbation 5, 5 months after vaccination, requiring GC dose escalation from 4 to 8 mg/day. Casual relationship of this exacerbation with vaccination was very unlikely. Conclusions: Thus preliminary results are indicative of good 23-valent pneumococcal vaccine tolerability in SLE patients. Further studies are required for comprehensive assessment of vaccine efficacy and safety in this group of patients. Disclosure of Interest: None declared